Rekonstruksi Destinasi Wisata Selo Bonang Desa Panduman Berbasis Geopark Argopuro Purba - Aprillianto, Bayu; Wahyuni, Nining Ika; Apriono, Markus; Fadah, Isti; Wilantari, Regina Niken; Pratama, Theodicy Kristian; Adhani, Brilian Farel; Agustriono, Aldi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Selo Bonang is a tourist destination in Panduman Village, Jember Regency, which has iconic potential, namely a stone site that produces notes, known as the